Life without children : [large type] stories - Doyle, Roddy, 1958- (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"Love and marriage. Children and family. Death and grief. Life touches everyone the same. But living under lockdown, it changes us alone. In these ten beautifully moving short stories written mostly over the last year, Booker Prize winner Roddy Doyle paints a collective portrait of our strange times. A man abroad wanders the stag-and-hen-strewn streets of Newcastle, as news of the virus at home asks him to question his next move. An exhausted nurse struggles to let go, having lost a much-loved patient in isolation. A middle-aged son, barred from his mother's funeral, wakes to an oncoming hangover of regret. Told with Doyle's signature warmth, wit, and extraordinary eye for the richness that underpins the quiet of our lives, Life Without Children cuts to the heart of how we are all navigating loss, loneliness, and the shifting of history underneath our feet"--